EP.FRI.12Meta-analysis of demographic and prognostic significance of right-sided versus left-sided acute diverticulitis. (28th October 2021) - Hajibandeh, Shahab; Hajibandeh, Shahin; Smart, Neil J; Maw, Andrew
Abstract: Aims: To compare the demographic and prognostic outcomes of right-sided versus left-sided acute colonic diverticulitis Methods: We performed a systematic review in accordance with the PRISMA statement standards to identify all observational studies comparing demographic factors and outcomes of right-sided versus left-sided acute colonic diverticulitis. We used the ROBINS-I tool to assess the risk of bias of included studies. Random effects modelling was applied to calculate pooled outcome data. Results: Analysis of 2933 patients from nine studies suggests that right-sided diverticulitis affects younger patients (MD:-14.16, P<0.00001) and more male patients (OR:1.33, P=0.02) compared with left-sided diverticulitis. Smoking (OR:2.23, P<0.0001), alcohol consumption (OR:1.85, P=0.002) and co-morbidity (OR:0.21, P<0.00001) were more common in patients with right-sided diverticulitis. The risk of complicated diverticulitis was lower in the right-sided group (OR:0.21, P=0.001). More patients in the right-sided diverticulitis group had modified Hinchey stage I disease (OR:10.21, P<0.0001) while more patients in the left-sided group had stage II (OR:0.19, P<0.00001), stage III (OR:0.08, P=0.009) or stage IV disease (OR:0.02, P<0.00001). Right-sided diverticulitis was associated with a lower risk of recurrence (OR:0.49, P=0.04), failure of conservative management (OR:0.14, P=0.0006), the need for emergency surgery (OR:0.13, <0.00001) and shorter length of hospital stay (MD:-1.70, P=0.02). Conclusions: Right-sided acute colonic diverticulitis predominantly affects younger male patients compared with left-sided disease and is associated with favourable outcomes as indicated by the lower risk of complications, failure of conservative management, need for emergency surgery, recurrence, and shorter length of hospital stay. More studies are required to compare the postoperative outcomes in patients with right-sided and left-sided diverticulitis undergoing emergency surgery.